Inequality thresholds, governance and gender economic inclusion in sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
Inequality and gender economic exclusion are major policy concerns facing sub-Saharan Africa in the post-2015 development agenda. The study provides critical masses of inequality that should not be exceeded if governance is to promote gender economic participation. The research focuses on 42 countries in sub-Saharan Africa using annual data spanning from 2004 to 2014. The empirical evidence is based on the Generalized Method of Moments. The following findings are established. First, inequality (i.e. the Gini coefficient) levels that completely nullify the positive effect of governance on female labour force participation are 0.708 for political stability, 0.601 for voice & accountability, 0.588 for government effectiveness, 0.631 for regulatory quality, 0.612 for the rule of law, and 0.550 for corruption control. Second, inequality thresholds at which female unemployment can no longer be mitigated by governance channels include: 0.561 (for political stability) and 0.465 (for the rule of law). Third, inequality levels that completely dampen the positive impact of governance on female employment are 0.608 for political stability, 0.580 for voice & accountability, 0.581 for government effectiveness, and 0.557 for the rule of law. As the main policy implication, for good governance to promote gender economic inclusion, inequality levels should not exceed established thresholds.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Gender; Inequality; Inclusive development